Government spending shocks and the multiplier: New evidence from the US based on natural disasters - Weonho Yang; Jan Fidrmuc; Sugata Ghosh (Center for Economic Studies and ifo Institute (CESifo), 2012)
The literature on estimating macroeconomic effects of fiscal policy requires suitable instruments to identify exogenous and unanticipated spending shocks. So far, the instrument of choice has been military build-ups. This instrument, however, largely limits the analysis to the US as few other countries have been involved in mainly extraterritorial conflicts. Moreover, the expenditure associated with military build-ups affects primarily the defense sector so that the resulting multiplier does not necessarily approximate the effects of changes to general government spending. We propose an alternative instrument: government relief expenditure in the wake of natural disasters which is more similar in its scope to general government spending. We construct a rich data set of natural disasters and the corresponding government responses at the US state level. We apply this methodology both at the state as well as national levels and show that natural disasters serve as a powerful instrument for identifying government spending shocks. Furthermore, we show that the multiplier pertaining to non-defense government spending is higher than the defense-spending multiplier estimated in the literature using military build-ups.
Keywords: E22; E62; H30; H50; H72; 330; fiscal shocks; narrative approach; fiscal multiplier; natural disaster